Fissure evolution and variation of pyrolysis kinetics parameters of tar-rich coal during heat treatment under different atmosphere - Shuangming WANG; Qiang SUN; Xin HU; Zhenlong GE; Jishi GENG; Shengze XUE; Qingmin SHI (Meitan kexue jishu, 2024)
The clean and efficient development of tar-rich coal is helpful in ensuring China's energy security. The tar-rich coal from Ningtiaota Mine was selected and heated under N2 and hypoxia atmosphere. Using a stereomicroscope to obtain the apparent morphology of tar-rich coal treated at different temperatures, the thermal gravimetric (TG), differential scanning calorimetry (DSC), and differential scanning calorimetry (DTG) of tar-rich coal were tested at 0-600 ℃ in an argon atmosphere. Based on the laser flash method, the thermal conductivity changes of tar-rich coal were monitored, and the changes in pyrolysis kinetics parameters such as activation energy and frequency factor under different heating rates were analyzed. The crack evolution and pyrolysis kinetics parameter variation of tar-rich coal after heat treatment were explored. The results show that with the increase of heating temperature, the number of cracks on the surface of the tar-rich coal sample increases significantly and gradually. Additionally, the degree of fracture development in vitrain is higher. Compared with the N2 atmosphere, the crack rate of coal samples in the hypoxia atmosphere at the same temperature is higher. The changing trend of mass loss ratio is similar to the trend of fracture rate, and the growth rate is faster due to the oxidation reaction of coal samples in the hypoxia environment. The temperature at which the mass loss rate and fracture rate of tar-rich coal rapidly increase in the N2 atmosphere is clearly lagging behind that in the hypoxia atmosphere. In the range of room temperature to 350 ℃, due to the effect of thermal expansion, the thermal conductivity of tar-rich coal increases with the increase of temperature. According to TG analysis, the tar-rich coal can be divided into three stages with temperature changes: 25-300 ℃, 300-500 ℃ and 500-600 ℃. In stages I and II, due to the precipitation of adsorbed water and the heat absorption of organic matter decomposition, the frequency factor and activation energy gradually increase; In stage III, due to the exothermic decomposition of inorganic minerals, the frequency factor and activation energy decrease. The results are help understand the structural evolution mechanism and heat transfer mechanism of tar-rich coal in the process of high temperature development.